2009
DOI: 10.3892/mmr_00000110
|View full text |Cite
|
Sign up to set email alerts
|

Localization and characterization of γ-glutamyl cyclotransferase in cancer cells

Abstract: Abstract.Using differential display analysis, we have identified a novel rat gene whose expression is increased during tumor progression in rat mammary carcinoma cell lines. This gene is an ortholog of the human chromosome 7 open reading frame 24 gene (C7orf24) and encodes a protein of 188 amino acids with no recognized protein domains. C7orf24 has been identified as Á-glutamyl cyclotransferase (GGCT), an important enzyme functioning in glutathione homeostasis. Our Northern and Western blot analyses revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 9 publications
4
6
0
Order By: Relevance
“…The intracellular distribution found by immunohistochemistry was in the cytoplasm and nucleus and these findings were almost consistent with a few other reports [ 12 14 ]. Cytoplasmic staining by immunohistochemistry is relatively homogeneous.…”
Section: Distribution and Intracellular Localization Of Ggct In Nosupporting
confidence: 93%
See 2 more Smart Citations
“…The intracellular distribution found by immunohistochemistry was in the cytoplasm and nucleus and these findings were almost consistent with a few other reports [ 12 14 ]. Cytoplasmic staining by immunohistochemistry is relatively homogeneous.…”
Section: Distribution and Intracellular Localization Of Ggct In Nosupporting
confidence: 93%
“…However, no significant changes were observed in comparison with controls [ 7 ]. Independently of our work, Azumi et al also reported findings similar to our results by introducing the GGCT gene into HBL-100 cells, a breast cancer cell line with low-level GGCT expression [ 14 ]. Thus, it is assumed that the involvement of GGCT in malignant transformation was negated.…”
Section: Role Of Ggct In Cancer Cellssupporting
confidence: 88%
See 1 more Smart Citation
“…Based on theanalysis of two independent studies in Oncomine database, we found that GGCT is highly accumulated in gastric cancer cells. Furthermore, it has beenproved thatGGCTfunctioned as a novel biomarker of esophageal squamous malignancies, as its expression levels strongly correlated with lymph node metastasis and differentiation degree [611], in consistent with that overexpression and depletion of GGCT resulted in proliferative and antiproliferative activities in bladder cancer cells, respectively [9]. Here, we observed that GGCT depletion could remarkably inhibit cell proliferation and colony formation activities ofhuman gastric cancer cells.…”
Section: Discussionsupporting
confidence: 83%
“…In a previous study of the intracellular distribution of GGCT, a green fluorescent protein-GGCT fusion protein was only detected in the cytoplasm. However, a deletion mutant lacking GGCT residues 61-120 was localized to the nucleus, suggesting that the central region is required to anchor GGCT in the cytoplasm (Azumi et al 2009). In the present study, we noted that GGCT is sometimes detected in the nucleus of human cells, and we also noted a lower molecular weight variant in some tissues.…”
Section: Discussionmentioning
confidence: 99%